Effect of a Fast-Skin body suit on drag during front crawl swimming - Toussaint, H. M.; Truijens, M.; Elzinga, M.-J.; van de Ven, A.; de Best, H.; Snabel, B.; de Groot, G. (Sports Biomechanics, 2002)
The effect on drag of a Speedo Fast-skin suit compared to a conventional suit was studied in 13 subjects (6 males, 7 females) swimming at different velocities between 1.0 and 2.0 ms-1. The active drag force was directly measured during front crawl swimming using a system of underwater push-off pads instrumented with a force transducer (MAD system). For a range of swimming speeds (1.1, 1.3, 1.5 and 1.7 ms-1), drag values were estimated. On a group level, a statistically non-significant drag reduction effect of 2% was observed for the Fast-skin suit (p = 0.31). Therefore, the 7.5% reduction in drag claimed by the swimwear manufacturer was not corroborated.